POLARIZED PARTIAL FREQUENCY REDISTRIBUTION IN SUBORDINATE LINES. II. SOLUTION OF THE TRANSFER EQUATION WITH RAYLEIGH SCATTERING - Nagendra, K. N.; Sampoorna, M. (The Astrophysical journal, 2012)
It is quite common in line formation theory to treat scattering in subordinate lines under the assumption of complete frequency redistribution (CRD). The partial frequency redistribution (PRD) in subordinate lines cannot always be approximated by CRD, especially when the polarization state of the line radiation is taken into account. Here we investigate the PRD effects in subordinate lines including scattering polarization. The line formation is described by a polarized non-LTE line transfer equation based on a two-level atom model. We use the recently derived subordinate line redistribution matrix. We devise polarized approximate lambda iteration methods to solve the concerned transfer problem. The linear polarization profiles of subordinate lines formed in non-magnetic (Rayleigh) scattering atmospheres are discussed. We consider one-dimensional isothermal planar model atmospheres. We show that in the polarized line transfer calculations of subordinate lines, PRD plays as important of a role as it does in the case of resonance lines. We also study the effect of collisions on linear polarization profiles of subordinate lines.